The Catastrophe Revisited: Blood Compatibility in the 21(st) Century - Ratner, Buddy D. (2007)
The biomaterials community has been unable to accurately assign the term “blood compatible” to a biomaterial in spite of 50 years of intensive research on the subject. There is no clear consensus as to which materials are “blood compatible.” There are no standardized methods to assess blood compatibility. Since we use millions of devices in contact with blood each year, it is imperative we give serious thought to this intellectual catastrophe. In this perspective, I consider five hypotheses as to why progress has been slow in evolving a clear understanding of blood compatibility: Hypothesis 1 -- It is impossible to make a blood compatible material. Hypothesis 2 -- We do not understand the biology behind blood compatibility. Hypothesis 3 -- We do not understand how to test for or evaluate blood compatibility. Hypothesis 4 -- Certain materials of natural origin seem to show better blood compatibility but we do not know how to exploit this concept. Hypothesis 5 -- We now have better blood compatible materials but the regulatory and economic climate prevent adoption in clinical practice.